Peran Guru Kelas Dalam Menumbuhkan Rasa Percaya Diri Peserta Didik Kelas IVA Di Madrasah Ibtidaiyah Negeri 6 Sinar Rejeki Lampung Selatan - Khusna Nazila; Etika Pujianti; Alfi Zahrotul Hamidah (Journal on Education, 2024)
Self-confidence is possessed by everyone, including students at Madrasah Ibtidaiyah. Self-confidence is very much needed by students in learning so that it can motivate students to achieve achievements in learning. However, not all students have sufficient self-confidence. Feelings of inferiority, shame, fear and others can be obstacles for students in interacting both in the learning process at school and in the community. The results of initial observations at MIN 6 South Lampung revealed that in the learning process there were still students who were classified as having low self-confidence. The problems in this study are a). how is the role of class teachers in fostering students' self-confidence at MIN 6 South Lampung and b). what obstacles do teachers face in carrying out their roles. This type of research, namely field research/descriptive qualitative, is research that is conducted directly in the field using a case study research design. The data collection techniques are observation, interviews, and documentation. The data analysis techniques are data reduction, data presentation, and drawing conclusions. While the data validity technique is the extension of researcher participation and triangulation. The results of this study are: First, the role of class teachers in fostering students' self-confidence at MIN 6 South Lampung, namely: a) Teachers as motivators by providing motivation to students; b) Teachers as inspirators by providing appreciation to students; c) Teachers as mentors by inviting students to actively communicate; d) Teachers as organizers by giving special responsibilities to students who have low self-confidence; and e) Teachers as class managers by arranging student seating; Second, the obstacles faced by class teachers in carrying out their role to foster students' self-confidence at MIN 6 South Lampung include some subject teachers who are less involved in developing students' self-confidence, some parents of students who are less supportive of the actions taken by class teachers to develop students' self-confidence, and some students who are difficult to communicate with and too withdrawn so that teachers have difficulty taking action that is appropriate to the conditions of the students concern